2013
DOI: 10.11606/issn.2176-7262.v46i1p36-46
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da contribuição do aparelho de amplificação sonora no espectro da neuropatia auditiva: um estudo de caso

Abstract: Modelo do estudo: Estudo de caso. Objetivo do estudo: Verificar a contribuição da adaptação do aparelho de amplificação sonora (AAS) em duas pacientes adultas com diagnóstico de Espectro de Neuropatia Auditiva (ENA), em relação às habilidades auditivas e de comunicação. Importância do problema: Indivíduos diagnosticados com ENA apresentam sintomatologia clínica variada com queixa predominante de dificuldade de discriminação de fala, principalmente em ambientes ruidosos e, a literatura, aponta várias possibilid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Thus, we believe that HA use in this patient with ANSD mainly contributed to the relief of the major complaint of affected individuals (i.e., auditory speech perception in a noisy environment). 5 10 12 13 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we believe that HA use in this patient with ANSD mainly contributed to the relief of the major complaint of affected individuals (i.e., auditory speech perception in a noisy environment). 5 10 12 13 …”
Section: Discussionmentioning
confidence: 99%
“…The present findings agree with previous reports that suggested that, if the use of the HA shows some benefit in free field tests, in speech perception tests, or in terms of the user's self-evaluation, its use should be considered positive. 5 10 12 On this basis, new strategies should be added or modified to improve speech comprehension and communication.…”
Section: Discussionmentioning
confidence: 99%